2011
DOI: 10.1371/journal.pone.0022046
|View full text |Cite
|
Sign up to set email alerts
|

Spliceosomal Intron Insertions in Genome Compacted Ray-Finned Fishes as Evident from Phylogeny of MC Receptors, Also Supported by a Few Other GPCRs

Abstract: BackgroundInsertions of spliceosomal introns are very rare events during evolution of vertebrates and the mechanisms governing creation of novel intron(s) remain obscure. Largely, gene structures of melanocortin (MC) receptors are characterized by intron-less architecture. However, recently a few exceptions have been reported in some fishes. This warrants a systematic survey of MC receptors for understanding intron insertion events during vertebrate evolution.Methodology/Principal FindingsWe have compiled an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 108 publications
(155 reference statements)
2
13
0
Order By: Relevance
“…Recently, we have reported that TRPV1 is a highly conserved protein throughout the evolution. 23 Endogenous expression and involvement of TRPV1 in the sperm cells from different species is in full agreement with its conservation at the protein as well as in the genome level.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, we have reported that TRPV1 is a highly conserved protein throughout the evolution. 23 Endogenous expression and involvement of TRPV1 in the sperm cells from different species is in full agreement with its conservation at the protein as well as in the genome level.…”
Section: Discussionsupporting
confidence: 62%
“…Whereas the exon–intron division is a relatively well-conserved feature of closely related genes, addition or deletion of introns occurs at a frequency of ca. 1 intron/gene every 100 million years ( 38 40 ), and such events are common in many fish ( 41 , 42 ). The fact that much of the other observed differences in mRNA size could be attributed to changes in the length of non-coding sequences, and not changes within the open reading frame, may also serve to explain the high tolerance to these significant insertions/deletions since these regions are less subject to functional constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Since we included the first intron of both genes in our constructs, we also tested for similarities within these sequences. In the lhb introns, a specific sequence of putative binding motifs was found in both zebrafish and tilapia, although the motifs were more densely distributed in the tilapia, corresponding to the trend toward a more compact genome in tilapia than in zebrafish ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fish, the number, affinity, specificity, tissue distribution and the physiological roles are far from defined and appear to be species-specific. For example, pufferfish (Tetraodon nigroviridis) has only four receptors lacking Mc3r (Schiöth et al, 2005), while zebrafish has six receptors with two copies of Mc5r (Kumar et al, 2011). The larger number of Mcr paralogs found in some teleost species probably originated in the extra round of whole genome duplication that occurred during early teleost evolution…”
Section: Melanocortin Receptorsmentioning
confidence: 99%